Twenty Years after IIRIRA: The Rise of Immigrant Detention and its Effects on Latinx Communities across the Nation. (2018) - Juárez, Melina; Gómez-Aguiñaga, Bárbara; Bettez, Sonia P.
This paper studies the dynamics of detention, deportation, and the criminalization of immigrants. We ground our analyses and discussion around the Illegal Immigration Reform and Immigrant Responsibility Act of 1996's (IIRIRA's) detention mandate, the role of special interest groups and federal policies. We argue that these special interest groups and major federal policies have come together to fuel the expansion of immigrant detention to unprecedented levels. Moreover, we aim to incite discussion on what this rapid growth in detention means for human rights, legislative representation and democracy in the United States. This study analyzes two main questions: What is the role of special interests in the criminalization of immigrants? And does the rapid increase in detention pose challenges or risks to democracy in the United States? Our study is grounded within the limited, yet growing literature on immigrant detention, government data, and "gray" literature produced by nonprofits and organizations working on immigration-related issues. We construct a unique dataset using this literature and congressional reports to assess what factors are associated with the rise of immigrant detention. A series of correlations and a time series regression analysis reveal that major restrictive federal immigration policies such as IIRIRA, along with the increasing federal immigration enforcement budget, have had a significant impact on immigrant detention rates. Based on these findings, we recommend three central policy actions. First, the paper recommends increased transparency and accountability on behalf of the Department of omeland Security, Immigration and Customs Enforcement, and on lobbying expenditures from for-profit detention corporations. Second, it argues for the repeal of mandatory detention laws. These mandatory laws have led to the further criminalization and marginalization of undocumented immigrants. And lastly, it argues that repeal of the Congressional bed mandate would allow for the number of detainees to mirror actual detention needs, rather than providing an incentive to detain. However, we anticipate that the demand for beds will increase even more given the current administration's push for the criminalization and increased arrests of undocumented individuals. The rhetoric used by the present administration further criminalizes immigrants. 1